Comparison of quantitative atherosclerotic plaque burden from coronary CT angiography in patients with first acute coronary syndrome and stable coronary artery disease - Dey, Damini; Achenbach, Stephan; Schuhbaeck, Annika; Pflederer, Tobias; Nakazato, Ryo; Slomka, Piotr J.; Berman, Daniel S.; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2014)
Coronary CTA allows characterization of non-calcified and calcified plaque and identification of high-risk plaque features.We aimed to quantitatively characterize and compare coronary plaque burden from CTA in patients with a first acute coronary syndrome (ACS) and controls with stable coronary artery disease.We retrospectively analyzed consecutive patients with non-ST-segment elevation myocardial infarction (NSTEMI) or unstable angina with a first ACS, who underwent CTA as part of their initial workup before invasive coronary angiography and age- and gender-matched controls with stable chest pain; controls also underwent CTA with subsequent invasive angiography (total n = 28). Culprit arteries were identified in ACS patients. Coronary arteries were analyzed by automated software to quantify calcified plaque (CP), noncalcified plaque (NCP), and low-density NCP (LD-NCP, attenuation <30 Hounsfield units) volumes, and corresponding burden (plaque volume × 100%/vessel volume), stenosis, remodeling index, contrast density difference (maximum percent difference in attenuation/cross-sectional area from proximal cross-section), and plaque length.ACS patients had fewer lesions (median, 1), with higher total NCP and LD-NCP burdens (NCP: 57.4% vs 41.5%; LD-NCP: 12.5% vs 8%; P <= .04), higher maximal stenoses (85.6% vs 53.0%; P = .003) and contrast density differences (46.1 vs 16.3%; P < .006). Per-patient CP burden was not different between ACS and controls. NCP and LD-NCP plaque burden was higher in culprit vs nonculprit arteries (NCP: 57.8% vs 9.5%; LD-NCP: 8.4% vs 0.6%; P <= .0003); CP was not significantly different. Culprit arteries had increased plaque lengths, remodeling indices, stenoses, and contrast density differences (46.1% vs 10.9%; P <= .001).Noninvasive quantitative coronary artery analysis identified several differences for ACS, both on per-patient and per-vessel basis, including increased NCP, LD-NCP burden, and contrast density difference.
EVALuna2:11863